Avalição in vitro das atividades citotóxicas e genotóxicas de um metalocomplexo à base de cobre (II) denominado Dri-12 - Machado, Pedro Henrique Alves (2019)
Cancer is a huge public health issue, which leads to millions of deaths every year, thus requiring more effective therapy approaches. Chemotherapy is one of the most common methods for treating neoplasia and, since the discovery of cisplatin; the search for metal complexes has been increasing. In this context, copper has been gaining notoriety, since it is an essential micronutrient for vital functions and participates in several biological processes. According to studies, tumor cells have shown high copper concentrations when compared to healthy cells, which provides possible advantages to working with this transition metal. Furthermore, copper possesses active redox, granting it the potential to produce ROS (Reactive oxygen species), which is the main action mechanism of copper (II) based metal complexes. When complexed too other ligands, copper has shown the ability to cleave DNA, thus boosting the development of various metal complexes that could possess anti-tumor potential. In this context, this work has described the in vitro anti-tumor potential of a copper based metal complex Copper (II) linked to 4-Fluorophenoxyacetic acid hydrazide and 1,10-Phenanthroline] Dri-12. This metal complex has displayed the capacity to induce ROS production, being possibly the main mechanism responsible for DNA damage, stopping tumor cells at the G0/G1 stage of the cell cycle, therefore inducing programmed cell death. When compared to cisplatin and other copper-based metal complexes, Dri-12 has displayed better selectivity rates, preferring to act on tumor cells instead of healthy cells. Due to its in-vivo anti-tumor action, the copper complex Dri-12 becomes a promising candidate to anti-tumor agent.